Internet use and rural-urban mental health inequalities: Evidence from China - Weihao Nie; Mingzheng Hu; Xin Ye (Frontiers Media S.A., 2023)
IntroductionIn the context of the new digital era, clarifying the relationship between Internet use and urban and rural residents' mental health is of important value for reducing rural-urban health inequalities. This paper aims to study the association between Internet use and rural-urban mental health inequalities.MethodsBased on the data of the China Family Panel Studies (CFPS) in 2020, we firstly examined the existence and specific manifestation of mental health inequalities between urban and rural residents. Secondly, we examined the mediating effect of Internet use by the Bootstrap mediating effect measure. Finally, we verified the robustness of the mediating effect.ResultsThere are significant mental health inequalities between urban and rural residents, and urban residents have better mental health than rural residents (p < 0.01). In addition, the test results for the mediating effect of Internet use on mental health inequalities between urban and rural residents were significant (p < 0.01), with a direct effect of −0.028 (p < 0.01) and an indirect effect of −0.49 (p < 0.01), and this result remained significant in the robustness test.DiscussionIn such a new age of the Internet, mental health inequalities between urban and rural residents objectively did exist, and the use of the internet played a positive mediation effect on the formation of mental health inequalities between urban and rural areas.